One-pot synthesis of manganese oxides and cobalt phosphides nanohybrids with abundant heterointerfaces in an amorphous matrix for efficient hydrogen evolution in alkaline solution. Issue 39 (26th September 2019) - Zhou, Dan; Wang, Zheng; Long, Xia; An, Yiming; Lin, He; Xing, Zheng; Ma, Ming; Yang, Shihe
Abstract : In this study, we prepared a nanohybrid of manganese oxides and cobalt phosphides and demonstrated that the interface is accounted for its superior activity. Abstract : Transition metal phosphides (TMPs), albeit promising as hydrogen evolution reaction (HER) catalysts, suffer from a sluggish water dissociation step in alkaline solutions. Metal oxides(hydroxides) have been employed to address this problem by providing an additional driving force, but the active interface between metal oxides(hydroxides) and phosphides is limited, leading to unsatisfactory catalytic efficiencies. Herein, we report a highly efficient HER catalyst, comprising a hybrid nanosheet array of manganese oxides and cobalt phosphides (denoted as Mn–O@Co–P) with numerous nanoheterointerfaces, facilely grown on carbon cloth (CC) by a simple one-pot process. The obtained Mn–O@Co–P/CC showed superior HER activity in alkaline solution, with a low overpotential of 106 mV at 10 mA cm −2, a small Tafel slope of 56 mV dec −1 and excellent long-term durability. More importantly, this study demonstrates that Mn was not doped into the cobalt phosphide, but formed interfaces between metal oxides and cobalt phosphides. DFT calculations indicate that the interface between Mn–O and Co–P can act as a frustrated Lewis-pair and significantly increase the driving force for water splitting by stabilizing the separated hydride and hydroxide, thereby facilitating the HER in alkaline conditions.